16.5% - Hill, Natasha (Te Kaharoa, 2020)
My name is Gabriella Campbell and I am a white Māori. Growing up, this is what I heard from my classmates and teachers. The way I acted, behaved or dressed most likely convinced most of them I was white. I mean seriously, just because my skin is a shade lighter than the ‘real’ Māori kids, doesn’t mean I can’t be one of them. In fact, I was probably one of the few Māori kids at my school, which was located right in the middle of other high decile schools around Auckland.  St Helinbergs was where it began.